Evaluation of Training Programmme on Integrated Watershed Management Programme in Jammu and Kashmir - GUPTA, N. K.; MANHAS, J. S.; RANI, B. RENUKA (Journal of Soil and Water Conservation, 2020)
AbstractÂ